Professional Improvement - Basil T. Sheahan (Journal of Applied Communications, 1982)
Professional Improvement: Summary of Survey Findings. A questionnaire was mailed to agricultural communication major graduates from the University of Illinois. The objectives were to determine professional development improvement activities...